2017
DOI: 10.1063/1.5006269
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion crystals: Dynamics and phase transition

Abstract: We study a crystal of skyrmions generated on a square lattice using a ferromagnetic exchange interaction and a Dzyaloshinskii-Moriya interaction between nearest-neighbors under an external magnetic field. The skyrmion crystal has a hexagonal structure which is shown to be stable up to a temperature Tc where a transition to the paramagnetic phase occur. We will show that the dynamics of the skyrmions at T < Tc follows a stretched exponential law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A necessary condition for the existence of skyrmions in bulk samples was the absence of an inverse transformation in the crystal magnetic symmetry group. Diep et al 12 have studied a crystal of skyrmions generated on a square lattice using a ferromagnetic exchange interaction and a Dzyaloshinskii-Moriya interaction between nearest-neighbors under an external magnetic field. They have shown that the skyrmion crystal has a hexagonal structure which is shown to be stable up to a temperature T c where a transition to the paramagnetic phase occurs and the dynamics of the skyrmions at T < T c follows a stretched exponential law.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A necessary condition for the existence of skyrmions in bulk samples was the absence of an inverse transformation in the crystal magnetic symmetry group. Diep et al 12 have studied a crystal of skyrmions generated on a square lattice using a ferromagnetic exchange interaction and a Dzyaloshinskii-Moriya interaction between nearest-neighbors under an external magnetic field. They have shown that the skyrmion crystal has a hexagonal structure which is shown to be stable up to a temperature T c where a transition to the paramagnetic phase occurs and the dynamics of the skyrmions at T < T c follows a stretched exponential law.…”
Section: Introductionmentioning
confidence: 99%
“…11 it was shown that the most extensive class of candidates for the detection of skyrmions includes the surfaces and interfaces of magnetic materials, where the geometry of the material breaks the central symmetry and, therefore, can lead to the appearance of chiral interactions similar to the Dzyaloshinskii-Moriya interaction. In addition, skyrmions are two-dimensional solitons, the stability of which is provided by the local competition of short-range interactions exchange and Dzyaloshinskii-Moriya interactions 12,13 . The idea of using skyrmions in memory devices nowadays is reduced to the information encoding using the presence or absence of a skyrmion in certain area of the Surface spin configuration is calculated by minimizing the spin interaction energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude this section, let us emphasize that beyond the two models for interface coupling studied above, the Dzyaloshinskii-Moriya interface interaction of the form J mf P k · ( S i × S j ) may induce unexpected phenomena at the magneto-ferroelectric interface 28,29 . Work is under way to investigate this coupling model.…”
Section: Another Model Of Interface Interactionmentioning
confidence: 99%
“…The phenomenological Landau-Ginzburg model introduced by I. Dzyaloshinskii [25] was microscopically derived by T. Moriya [26]. The DM interaction has been shown to generate skyrmions in thin films [27][28][29] and in magneto-ferroelectric superlattices [30][31][32].…”
mentioning
confidence: 99%